2022
DOI: 10.1108/jmb-11-2021-0056
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining the best value for money through procurement planning: can procurement regulatory compliance intervene?

Abstract: PurposeWhile empirical studies establish the importance of procurement planning in achieving value for money (VfM) in procurement, there is scant evidence demonstrating a link between procurement planning and procurement regulatory compliance, and thus VfM. As a result, this study examined how procurement regulatory compliance can be applied when procurement practitioners in Tanzania seek to maximize VfM through procurement planning.Design/methodology/approachA cross-sectional research design was adopted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Bryman and Bell (2011) provide that variations and patterns of association can be found when more than one case is looked at, which is what cross-sectional studies do. Since the government movement from the business major city Dar-es-salaam to Dodoma as a capital city, the city has become an emerging market for SMEs who provide goods and services to a number of government entities and agencies (Changalima et al , 2022a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bryman and Bell (2011) provide that variations and patterns of association can be found when more than one case is looked at, which is what cross-sectional studies do. Since the government movement from the business major city Dar-es-salaam to Dodoma as a capital city, the city has become an emerging market for SMEs who provide goods and services to a number of government entities and agencies (Changalima et al , 2022a).…”
Section: Methodsmentioning
confidence: 99%
“…Since the government movement from the business major city Dar-es-salaam to Dodoma as a capital city, the city has become an emerging market for SMEs who provide goods and services to a number of government entities and agencies (Changalima et al, 2022a).…”
Section: Study Area Research Designmentioning
confidence: 99%
“…The article found an incomplete compliance to the procurement sections in the local government. From a differed study, Abdi and Juma (2022) scrutinized how PRC can be used when procurement experts in Tanzania aim to amplify value for money by exploring procurement planning. The research found that PRC suggestively mediates the association between procurement planning and value for money in procurement.…”
Section: Procurement Regulatory Compliance and Creative Accountingmentioning
confidence: 99%
“…The monetary value of public expenditure on procurement activities raises academic interest in a variety of public procurement areas in various contexts. As a result, there are literature streams on public procurement performance (Changalima, Mchopa and Ismail 2022;Changalima and Ismail 2019;Kiage 2013), small-and mediumenterprise participation in public procurement (Namagembe, Mpeera and Kalid 2021;Siwandeti et al 2021), and value for money in public procurement (Changalima, Ismail and Mwaiseje 2022;Mchopa 2015;Mchopa et al 2014;Mwaiseje and Changalima 2020;Panga, Mchopa and Kazungu 2015). These studies show that the function of public procurement remains an important research theme for studies on the African continent.…”
Section: Conceptual Overview Of Key Concepts Public Procurementmentioning
confidence: 99%